Analisis Kesulitan Belajar Bahasa Indonesia pada Siswa Sekolah Menengah Atas: Studi Kasus SMAN 1 Balikpapan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the learning difficulties in Bahasa Indonesia experienced by high school students as well as the contributing factors. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that students face difficulties in four language skills reading, writing, speaking, and listening. In reading, students struggle to understand the main ideas and the content of texts In writing, numerous spelling errors and poorly structured paragraphs were found; In speaking, students show a lack of confidence and limited vocabulary while in listening, students are often unfocused, making it difficult to grasp important information. These difficulties are influenced by internal factors such as low reading interest, lack of learning motivation, and limited vocabulary, as well as external factors such ad monotonous teaching methods and an unsupportive learning environment. Therefore, more varied learning strategies and the strengthening of literacy culture in schools are needed to improve students language proficiency